Malaysian government securities: the movement of interest rate, price and yield / Didy Narisa Ab. Rahim - Ab. Rahim, Didy Narisa (1995)
This project paper is mainly to study the movement of interest rate, the price factor and the yield performance of Malaysian Government Securities. Malaysian Government Securities is one of the fixed - income securities that are widely transacted in Malaysia. It is believed that all the above factors can be taken into consideration in managing risk. The results throw some fight to the question of the relationship between long term and short term rates and tools used in fixed - income securities.